2017
DOI: 10.1002/jnr.24060
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous progesterone is neuroprotective following injury to the male zebra finch brain

Abstract: The use of progesterone following brain injury has a controversial history. On one hand, some lab-based models have showed progesterone as being neuroprotective, but on the other, clinical trials have showed quite the opposite. One of many complaints that arose from this discrepancy was the lack of a diverse pool of animal models and paradigms employed during the preclinical phase. However, over the past decade, the zebra finch has emerged as an optimal organism for the study of steroid-mediated neuroprotectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
1
7
1
Order By: Relevance
“…Females may be using progesterone in combination with estradiol as neuroprotective steroids following injury. These results are compelling as we have previously found a role for progesterone in cell survival following TBI in the brain (105) and this supports a large body of research examining progesterone treatment following TBI (136,137). Interestingly, like with estradiol despite positive pre-clinical studies, larger clinical, and human trials of progesterone use following TBI have been unsuccessful (138).…”
Section: Hsd17b1 and Hsd17b2supporting
confidence: 57%
See 1 more Smart Citation
“…Females may be using progesterone in combination with estradiol as neuroprotective steroids following injury. These results are compelling as we have previously found a role for progesterone in cell survival following TBI in the brain (105) and this supports a large body of research examining progesterone treatment following TBI (136,137). Interestingly, like with estradiol despite positive pre-clinical studies, larger clinical, and human trials of progesterone use following TBI have been unsuccessful (138).…”
Section: Hsd17b1 and Hsd17b2supporting
confidence: 57%
“…Importantly, DHEA-S prevents against rodent hippocampal neuronal cell loss and damage observed following ischemia and stroke (102). Additionally, the progesterone precursor pregnenolone and pregnenolone-sulfate also exhibit neuroprotective benefits (103)(104)(105). More work is necessary to discern estrogen mediated STS effects vs. DHEA mediated ones following TBI.…”
Section: Steroid Sulfatasementioning
confidence: 99%
“…p38alpha and JNK1 are considered as stress-activated protein kinases that participate in the cellular response to metabolic and other (environmental) stress conditions such as hormones (Bengal et al 2020 ). Furthermore, p38 expression was previously shown to increase in the vertebrate CNS after progestogen treatment (Blackshear et al 2017 ). We have found that these molecules show significant quantitative changes during the progestogen exposure (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, P4 was non‐detectable in zebra finch entopallium. This was unexpected as treatment of P4 following injury decreases injury size in zebra finches over controls and increases expression of various genes associated with cell survival and neuroinflammation 56 . Furthermore, P4 in mice was upregulated 72 h following injury, but declined at 2 weeks 68 .…”
Section: Discussionmentioning
confidence: 99%